Work–family conflict among Black, White, and Hispanic men and women. Issue 4 (8th August 2017) - Ammons, Samantha K.; Dahlin, Eric C.; Edgell, Penny; Santo, Jonathan Bruce
ABSTRACT: Are there racial/ethnic differences in work–family conflict? Using a nationally representative survey of Americans, we analyze differences in work–family conflict among Blacks, Whites, and Hispanics and then utilize an intersectional approach, disaggregating men and women within each racial/ethnic group. Using structural equation modeling, we find that the usual predictors of conflict – family and work characteristics – have varied effects on work–family conflict among men and women of different racial/ethnic groups. Nonstandard schedules were uniformly linked to increased work-to-family conflict among all respondents, regardless of subgroup. Our findings reveal the merits of intersectional approaches, and suggest the need for theoretical models of the work–family interface that better reflect the experiences of men and women of color.